(untitled) (Feni University Journal, 2026)
This study examines the gentleness and sensitivity with which Sharat Chandra Chattopadhyay portrays his female characters in Parineeta, Devdas, and Borodidi, reflecting the status of women in 20th-century Bengal society. The early 20th-century Bengal was not a liberating time for women, conventionally, as patriarchy and lack of autonomy and financial security played against women. However, Sharat Chandra presented many of his female characters with undeniable grace and strength, enabling them to navigate the limitations and hurdles of the patriarchal Bengal. His stories served as a critique of patriarchy and a celebration of women’s inner strength, while remaining grounded in reality. Practically, Sharat Chandra’s female characters are physically bound by society, but their emotional independence and determination provide them a sense of autonomy that surpasses physical restraints. This paper examines how, amidst the harrowing restrictions of living, his (Sharat’s) female characters utilise their agency and claim autonomy and independence, despite being confined within patriarchal limits. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (93-106)